ChemInform Abstract: PCl3‐Mediated Synthesis of Green/cyan Fluorescent Protein Chromophores Using Amino Acids. Issue 35 (11th August 2016) - Singh, Thokchom Prasanta; Shunmugam, Raja
Abstract: A convenient and rapid synthesis of green fluorescent protein (FP) chromophores (IV) and cyan FP chromophores (VI) starting from commercially available aromatic amino acids, acetyl chlorides, and anilines is described.